Des coiffes sans vécu ou l’authenticité rêvée - Pascale Dollfus (Ateliers d'Anthropologie)
In several European collections and on the art market, one finds beautiful headdresses that bear semi-precious stones and are stamped “Ladakh”. Yet although it is true that similar adornments are offered by many traders in Leh, after thirty years of research in this region of Himalaya and its surrounding area, as well as in archives, it has not been possible to find any trace of them. Then what are the origins of these atypical creations sold alongside unmysterious if not ordinary headdresses? How can they be characterised?Playing the detective, I attempt to reconstruct the journey taken by these mysterious objects by examining the market and its channels, and I explore the notion of authenticity and its underlying criteria in the area of so-called tribal or primitive art.